Awareness among the nursing staff regarding the administrative indicators to prevent the ventilator associated pneumonia - a prospective analysis - Fernandes, Sonal S.; P. M., Harish (International Journal Of Community Medicine And Public Health, 2025)
Background: Intensive care units is the heart of the hospital, ventilator associated pneumonia is a very common complication occurs patient with mechanical ventilators. Present study aimed to assess the awareness among nursing staff regarding the administrative indicators for the prevention of ventilator-associated pneumonia (VAP). Methods: A descriptive cross-sectional study was conducted in the Intensive care unit. Data was collected by 40 staff nurses posted in intensive care unit (ICU) by using a structured and validated questionnaire. The study was carried out over a period of two months, from September 2022 to October 2022. which included all eligible ICU nurses available during the study period. Nurses who were on leave, posted temporarily, or unwilling to participate were excluded from the study. Results: Result revealed that a majority of the participants (58.97%) were in the age group of 20–24 years, most respondents (71.80%) had completed B.Sc. Nursing and 56.41% of the nurses had between 1–3 years of experience. 92.31% of the nursing staff demonstrated good knowledge, 7.69% had an average level of knowledge on prevention of ventilator associated pneumonia. Conclusions: Although most staff demonstrated good knowledge about ventilator-associated pneumonia, the study’s limited sample size and scope to specific hospital areas restrict the generalizability of the findings. Future longitudinal studies could investigate the relationship between staff knowledge and clinical practice, as well as the impact of administrative factors on VAP prevention strategies.